Evaluasi Kesuksesan Penerapan Sistem Elektronik Kinerja (E-Kinerja) Menggunakan Enhanced Information System Success Model di Kecamatan Benda Tangerang - Latansa Amalia; Anik Hanifatul Azizah (JISKA (Jurnal Informatika Sunan Kalijaga), 2022)
E-Kinerja Benda District Tangerang City is an E-Government in the form of an Employee Performance Management Information System in charge of recording and reporting the performance of all employees in the government environment. The system should aim to simplify employee performance management and measure the efficiency and creativity of employees at work, in its implementation, there are still problems that occur. Many employees complain about the system, the implementation of the E-Kinerja system either directly or indirectly is considered troublesome, the internet network is not widely connected, the presence of technology devices (computers) is limited, and the lack of employees in understanding and utilizing the E-Kinerja system, and the lack of attendance and knowledge of information about IT as part of the supporting components in the process of presenting the information. So that an evaluation of the application of E-Kinerja is carried out, with the aim of this study being able to measure evaluation to prove the success rate of implementing E-Kinerja-based performance evaluations in Benda District, Tangerang City and knowing what factors or variables influence it. This study evaluates success using the Enhanced Information System Success Model with 7 evaluation variables: information quality, system quality, service quality, user satisfaction, trust, use, and net benefits. This study will use a qualitative and quantitative data approach through observation, interviews, literature studies, and questionnaires where the total respondents obtained are 62 respondents with PLS-SEM data analysis and SmartPLS 3.3 assistance. Based on the results of the research conducted, it is proven that from the 14 hypotheses proposed there are 5 hypotheses accepted while 9 other hypotheses are rejected. This evaluation also produces recommendations from the seven variables used which contain alternatives to improve and increase the success of the implementation of E-Kinerja.